Autoimmune and neuropsychiatric phenotypes in a Mecp2 transgenic mouse model on C57BL/6 background - Li, Yaxi; Zhang, Shu; Tang, Chenling; Yang, Bowen; Atrooz, Fatin; Ren, Zhifeng; Mohan, Chandra; Salim, Samina; Wu, Tianfu (Frontiers in Immunology, 2024)
Introduction Systemic Lupus Erythematosus (SLE) impacts the central nervous system (CNS), leading to severe neurological and psychiatric manifestations known as neuropsychiatric lupus (NPSLE). The complexity and heterogeneity of clinical presentations of NPSLE impede direct investigation of disease etiology in patients. The limitations of existing mouse models developed for NPSLE obstruct a comprehensive understanding of this disease. Hence, the identification of a robust mouse model of NPSLE is desirable. Methods C57BL/6 mice transgenic for human MeCP2 (B6.Mecp2Tg1) were phenotyped, including autoantibody profiling through antigen array, analysis of cellularity and activation of splenic immune cells through flow cytometry, and measurement of proteinuria. Behavioral tests were conducted to explore their neuropsychiatric functions. Immunofluorescence analyses were used to reveal altered neurogenesis and brain inflammation. Various signaling molecules implicated in lupus pathogenesis were examined using western blotting. Results B6.Mecp2Tg1 exhibits elevated proteinuria and an overall increase in autoantibodies, particularly in female B6.Mecp2Tg1 mice. An increase in CD3+CD4+ T cells in the transgenic mice was observed, along with activated germinal center cells and activated CD11b+F4/80+ macrophages. Moreover, the transgenic mice displayed reduced locomotor activity, heightened anxiety and depression, and impaired short-term memory. Immunofluorescence analysis revealed IgG deposition and immune cell infiltration in the kidneys and brains of transgenic mice, as well as altered neurogenesis, activated microglia, and compromised blood-brain barrier (BBB). Additionally, protein levels of various key signaling molecules were found to be differentially modulated upon MeCP2 overexpression, including GFAP, BDNF, Albumin, NCoR1, mTOR, and NLRP3. Discussion Collectively, this work demonstrates that B6.Mecp2Tg1 mice exhibit lupus-like phenotypes as well as robust CNS dysfunctions, suggesting its utility as a new animal model for NPSLE.